Antecedents of Destination Loyalty in Jakarta - Yonatan Stenly Sugiarto; Luki Adiati Pratomo (Value : Jurnal Manajemen dan Akuntansi, 2025)
The purpose of this study is to analyze whether there is a positive influence of service quality on electronic word of mouth, service quality on tourist satisfaction, quality of service on destination loyalty, electronic word of mouth on destination loyalty, and tourist satisfaction on destination loyalty. This research involves the use of structural Equation Modeling (SEM) analysis method as a statistical tool to process research data, while data processing uses software tools, namely SPSS 21 and AMOS 23. The sampling technique used is purposive sampling. The expected results in this study concluded that service quality has a positive effect on electronic word of mouth, service quality has a positive effect on tourist satisfaction, there is no positive effect of service quality on destination loyalty, electronic word of mouth has a positive effect on destination loyalty, tourist satisfaction has a positive effect on destination loyalty.